1989
DOI: 10.1149/1.2096581
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of Anodic Oxygen‐Transfer Reactions: Chronoamperometric and Voltammetric Studies of the Nucleation and Electrodeposition of β‐Lead Dioxide at a Rotated Gold Disk Electrode in Acidic Media

Abstract: The electrodeposition of 13-PbO2 from HC104 solutions of Pb(II) at an Au rotated disk electrode (RDE) was studied as a function of applied potential, rotational velocity, and the concentrations of HC104 and Pb(II). A long induction period (i.e., i = 0) is associated with high acidity, low concentration of Pb(II), and high rotational velocity. Following the induction period, the current rises to a steady-state value which is significantly lower than the mass transport-limited value for Pb(II). The steady-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…Several papers using experiments such as a rotating ring-disc electrode have demonstrated that a soluble (or colloidal) lead(IV) intermediate is involved in both the formation and dissolution of lead dioxide [47][48][49][50][51] and also the conversion of lead sulfate to lead dioxide. 52 Again, however, it is uncertain whether the Pb(IV) species is a short lived intermediate in the major pathway or formed in a minor side reaction.…”
Section: Deposition Of Lead Dioxide 31 Nucleation and Early Growthmentioning
confidence: 99%
“…Several papers using experiments such as a rotating ring-disc electrode have demonstrated that a soluble (or colloidal) lead(IV) intermediate is involved in both the formation and dissolution of lead dioxide [47][48][49][50][51] and also the conversion of lead sulfate to lead dioxide. 52 Again, however, it is uncertain whether the Pb(IV) species is a short lived intermediate in the major pathway or formed in a minor side reaction.…”
Section: Deposition Of Lead Dioxide 31 Nucleation and Early Growthmentioning
confidence: 99%
“…and therefore returning the cell and electrolyte to their initial conditions [10][11][12]. With the cell on open circuit, the electrolyte after 20 cycles was treated with 0.86 moles of hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…5A for F-PbO,/Ti RDE and a Fe-Pb02/F-PbO,/Ti RDE. The benefit of Fe(II1) in the oxide film is obvious in the region E 2 1.6 V. However, the activity is not as great as observed for Bi-PbQ/Au electrodes [6,16]. The voltammetric response for (CH,),SO at Ag-Bi-PbO,/Au electrodes is shown in Fig.…”
mentioning
confidence: 87%